(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Grounding the Freedom of Conscience in the Human Rights: Challenges Brought forth by the Emergence of the Posthuman Philosophy The freedom of conscience has been established as an important marker of democratic societies. The right of someone to choose and practice a certain religion has been stipulated in the domestic legislation of many countries, and also, internationally, from the First Amendment to the Constitution of the United States to the Universal Declaration of Human Rights. The freedom of conscience is based on two important pillars: the separation between religion and State and the meaning of the human nature itself. Someone has freedom of conscience precisely because he is human. But, what is a human, especially in a highly technological and globalized society as nowadays? Donna Haraway believes, in harmony with the posthuman philosophy, that we live in „a world of cyborgs” where „we are all chimeras, theorized and fabricated hybrids of machine and organism; in short, we are cyborgs”. In posthuman philosophy man is redefined regarding its own nature and, consequently, this weakens one of the pillars on which freedom of conscience rests upon: the human nature. Therefore, our goals in this paper are to explain the way in which the freedom of conscience had been established as a „human right”, and on the other side, to point out how this freedom is reshaped by the posthuman philosophy and what themes of reflection are brought to light by this topic.